Quantifying organic carbon storage in temperate pond sediments. (15th February 2021) - Gilbert, Peter J.; Taylor, Scott; Cooke, David A.; Deary, Michael E.; Jeffries, Michael J.
Abstract: Ponds may hold significant stocks of organic carbon in their sediments and pond creation may offer a practical application for land managers to increase carbon storage. However, ponds are overlooked in global carbon budgets. Their potential significance is suggested by the abundance of ponds throughout terrestrial biomes and their high carbon burial rates, but we lack measures of sediment carbon stocks from typical ponds. We sampled sediment from lowland temperate ponds in north east England comparing carbon stocks from ponds categorised by surrounding land use, or dominant vegetation, or drying regime, along with measures of variation within ponds. Sediment carbon varied considerably between ponds. This variation was more important than any systematic variation between pond types grouped by land use, vegetation or drying, or any variation within an individual pond. Our estimates of pond sediment organic carbon give measures that are higher than from soils in widespread habitats such as temperate grassland and woodland, suggesting that ponds are significant for carbon budgets in their own right. Ponds are relatively easy to create, are ubiquitous throughout temperate biomes and can be fitted in amongst other land uses; our results show that pond creation would be a useful and practical application to boost carbon sequestration in temperate landscapes. Graphical abstract: Image 1 Highlights: Organic carbon stored in pond sediments is missing from global carbon budgets. We quantified organic carbon in the sediment typical lowland temperate ponds. Carbon density varied markedly between individual ponds. Carbon density was higher than terrestrial habitats such as woodland and grassland. Ponds can be an important and practical carbon store.